Postgraduate students’ experiences during COVID-19 at an open distance learning institution - Maboe, K. A. (South African Journal of Higher Education, 2024)
Students’ research, interactivity, experiences, and exposure have increasingly become important indicators of quality in higher education, however these expectations declined during COVID-19 pandemic. While studies have been conducted on postgraduate students’ experiences during their studies, there is lack of empirical evidence on their experiences during COVID-19 pandemic, specifically at open distance learning institutions (ODLs). To bridge this identified gap, qualitative exploratory research was conducted to explore the experiences of postgraduate students registered in master’s and doctoral programmes at the Department of Health Studies, University of South Africa, during the pandemic. Non-probability purposive sampling was used. Online interviews via Microsoft Teams were used for data collection. The interviews were recorded and the data obtained were analysed thematically. Findings revealed both positive and negative experiences. Anxiety, exhaustion and frustration due to sickness, death of family members, poor communication from the university, inadequate resources and poor internet access affected students’ studies. Some participants reported lack of supervisory communication and support, while others applauded the continuous support of their supervisors and the university’s improvement of its electronic communication linkages. Microsoft Teams was newly adopted. Working from home also gave them an opportunity to accelerate their studies. In conclusion based on the findings the researcher recommended that the university continue to improve academic support and address the mental health of students to prepare them to accept current and future unforeseen circumstances positively. Strengthening collaboration with national and international partners to enhance continuous online communication between the university and the students should also be considered.